One-Pot Synthesis of Silver Nanoparticles Derived from Aqueous Leaf Extract of Ageratum conyzoides and Their Biological Efficacy - Deepak Paramasivam; Balamuralikrishnan Balasubramanian; Ramya Suresh; Jayanthi Kumaravelu; Manon Mani Vellingiri; Wen-Chao Liu; Arun Meyyazhagan; Amer M. Alanazi; Kannan R. R. Rengasamy; Vijaya Anand Arumugam (MDPI AG, 2023)
The main objective of the present research work is to assess the biological properties of the aqueous plant extract (ACAE) synthesised silver nanoparticles from the herbal plant Ageratum conyzoides, and their biological applications. The silver nanoparticle syntheses from Ageratum conyzoides (Ac-AgNPs) were optimised with different parameters, such as pH (2, 4, 6, 8 and 10) and varied silver nitrate concentration (1 mM and 5 mM). Based on the UV-vis spectroscopy analysis of the synthesised silver nanoparticles, the concentration of 5 mM with the pH at 8 was recorded as the peak reduction at 400 nm; and these conditions were optimized were used for further studies. The results of the FE-SEM analysis recorded the size ranges (~30-90 nm), and irregular spherical and triangular shapes of the AC-AgNPs were captured. The characterization reports of the HR-TEM investigation of AC-AgNPs were also in line with the FE-SEM studies. The antibacterial efficacies of AC-AgNPs have revealed the maximum zone of inhibition against S. typhi to be within 20 mm. The in vitro antiplasmodial activity of AC-AgNPs is shown to have an effective antiplasmodial property (IC50:17.65 μg/mL), whereas AgNO3 has shown a minimum level of IC50: value 68.03 μg/mL, and the Ac-AE showed >100 μg/mL at 24 h of parasitaemia suppression. The α-amylase inhibitory properties of AC-AgNPs have revealed a maximum inhibition similar to the control Acarbose (IC50: 10.87 μg/mL). The antioxidant activity of the AC-AgNPs have revealed a better property (87.86% ± 0.56, 85.95% ± 1.02 and 90.11 ± 0.29%) when compared with the Ac-AE and standard in all the three different tests, such as DPPH, FRAP and H2O2 scavenging assay, respectively. The current research work might be a baseline for the future drug expansion process in the area of nano-drug design, and its applications also has a lot of economic viability and is a safer method in synthesising or producing silver nanoparticles.